Milling of buckwheat hull to cell-scale: Influences on the behaviors of protein and starch in dough and noodles - Wang, Lijuan; Tang, Hanqi; Li, Yang; Guo, Zicong; Zou, Liang; Li, Zaigui; Qiu, Ju (Food chemistry, 2023)
[Display omitted] •Cell-scale fiber increased protein aggregation and starch gelatinization rate.•Cell-scale fiber decreased gluten malleability and starch thermal stability.•Fiber addition weakened the interaction between water and macromolecules.•Cell- and tissue-scale fiber differently affected spatial orderliness of protein.•Milling fiber to cell scale was conducive to improve the dough and noodle quality. Superfine grinding of insoluble dietary fiber (IDF) is a promising method to improve the product quality by regulating the interaction between protein and starch. In this study, the effects of buckwheat-hull IDF powder, at cell-scale (50–10 μm) and tissue-scale (500–100 μm), on the dough rheology and noodle quality were investigated. Results showed that cell-scale IDF with higher exposure of active groups increased the viscoelasticity and deformation resistance of the dough, due to the aggregation of protein–protein and protein-IDF. Compared with the control sample, the addition of tissue-scale or cell-scale IDF significantly increased the starch gelatinization rate (β, C3-C2) and decreased the starch hot-gel stability. Cell-scale IDF increased the rigid structure (β-sheet) of protein, thus improving the noodle texture. The decreased cooking quality of cell-scale IDF-fortified noodles was related to the poor stability of rigid gluten matrix and the weakened interaction between water and macromolecules (starch and protein) during cooking.